Improving access to help with poor sleep across youth mental health services: Interim implementation and clinical outcomes. - Rollinson, Rebecca; Ewing, Ben; Reeve, Sarah; Graham, Adam; Lyons, Jonathan; Gee, Brioney; Wilson, Jonathon; Tofan, Ioana; Semper, Kelly; Clarke, Tim (British Journal of Clinical Psychology, 2026)
Objectives: There is a high, unmet sleep need in young people with mental health difficulties. We took a whole‐system approach to improving access to sleep support across a youth mental health system (14–25 years). Methods: We used the Exploration, Preparation, Implementation and Sustainment (EPIS) framework to develop an implementation programme (The Better Sleep Programme) incorporating two levels of training: (i) therapeutic practitioners received training and supervision in CBT for insomnia (CBTi) adapted for young people with mental health difficulties, (ii) non‐therapeutic practitioners received knowledge and skills workshops. Implementation and clinical outcome measures were collected. Design: Implementation outcomes of acceptability, adoption, appropriateness, accessibility and fidelity were considered for the programme and CBTi intervention within it. Clinical outcomes for the CBTi intervention covered sleep, wellbeing and personal goals and were evaluated using a pre‐post comparison within‐subject design. Results: High levels of attendance and uptake were seen for CBTi training (210 therapeutic practitioners from 18 services) and workshops (270 attendees from 29 services). Five of the six core service areas trained were routinely offering the CBTi intervention. Significant improvements were seen across all clinical outcome measures (n = 83, p ≤ 0.001 to p ≤ 0.05) with moderate to large effect sizes observed across measures of sleep (d = 0.61–1.35), mental health (d = 0.57–1.26) and personal goals (d = 1.77). Conclusions: This centrally‐funded, system‐wide implementation programme shows significant promise as a means of improving sleep in young people with mental health difficulties. High uptake with encouraging clinical outcomes was seen across services. Further evaluation is required to establish sustainability and generalizability.